Improving the dissolution properties of curcumin using dense gas antisolvent technology - Kurniawansyah, F.; Quachie, L.; Mammucari, R.; Foster, Neil (Elsevier BV, 2017)
© 2017 Elsevier B.V. The dissolution properties of curcumin are notoriously poor and hinder its bioavailability. To improve its dissolution properties, curcumin has been formulated with methyl-ß-cyclodextrin and polyvinylpyrrolidone by the atomized rapid injection solvent extraction (ARISE) system. The compounds were co-precipitated from organic solutions using carbon dioxide at 30 °C and 95 bar as the antisolvent. Curcumin formulations were also produced by physical mixing and freeze drying for comparative purposes. The morphology, crystallinity, solid state molecular interactions, apparent solubility and dissolution profiles of samples were observed. The results indicate that the ARISE process is effective in the preparation of curcumin micro-composites with enhanced dissolution profiles compared to unprocessed material and products from physical mixing and freeze drying.